Leading from Within: The Effects of Emotion Recognition and Personality on Transformational Leadership Behavior - Rubin, Robert S.; Munz, David C.; Bommer, William H. (Academy of Management Journal, 2005)
This study of 145 managers of a large biotechnology/agricultural company examined how leaders' emotion recognition ability and personality characteristics influenced performance of transformational leadership behavior. Emotion recognition, positive affectivity, and agreeableness positively predicted such behavior. In addition, extra-version moderated the relationship between emotion recognition and transformational leadership. We also provided construct validity evidence for transformational leadership behavior by showing differing effects of these antecedents on contingent reward behavior. The study provides empirical support for the contribution of emotion and personality to transformational leadership behavior.